2018
DOI: 10.1113/ep086948
|View full text |Cite
|
Sign up to set email alerts
|

Metaboreceptor activation in heart failure with reduced ejection fraction: Linking cardiac and peripheral vascular haemodynamics

Abstract: We sought to evaluate the muscle metaboreflex in heart failure with reduced ejection fraction (HFrEF) patients, with an emphasis on the interaction between cardiac and peripheral vascular haemodynamics across multiple levels of metaboreceptor activation. In 23 HFrEF patients (63 ± 2 years of age) and 15 healthy control subjects (64 ± 3 years of age), we examined changes in mean arterial pressure, cardiac output, systemic vascular conductance, effective arterial elastance, stroke work and forearm deoxyhaemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Irrespective of augmented or blunted sympathetic responses to metaboreflex activation, most studies show a preserved BP increase to metaboreflex activation in HF (12,27,122,132). However, as previously reported in animal studies, HF individuals have an impaired capacity to increase SV and CO H95 during metaboreflex activation; thus the metaboreflex-mediated BP increase is largely dependent upon an increase in SVR (12,27,122,132,165).…”
Section: Studies In Humansmentioning
confidence: 84%
See 1 more Smart Citation
“…Irrespective of augmented or blunted sympathetic responses to metaboreflex activation, most studies show a preserved BP increase to metaboreflex activation in HF (12,27,122,132). However, as previously reported in animal studies, HF individuals have an impaired capacity to increase SV and CO H95 during metaboreflex activation; thus the metaboreflex-mediated BP increase is largely dependent upon an increase in SVR (12,27,122,132,165).…”
Section: Studies In Humansmentioning
confidence: 84%
“…Irrespective of augmented or blunted sympathetic responses to metaboreflex activation, most studies show a preserved BP increase to metaboreflex activation in HF (12,27,122,132). However, as previously reported in animal studies, HF individuals have an impaired capacity to increase SV and CO H95 during metaboreflex activation; thus the metaboreflex-mediated BP increase is largely dependent upon an increase in SVR (12,27,122,132,165). Accentuated peripheral vasoconstriction occurs in nonactive vascular beds (122) and in active muscle (3), with the latter reducing skeletal muscle perfusion during exercise, thereby increasing fatigue-related symptoms and stimulating further metaboreflex responses.…”
Section: Studies In Humansmentioning
confidence: 99%
“…While increased arterial pressure is primarily due to increased cardiac output in health, metaboreflex activation in HFrEF elicits negligible cardiac output changes and thus elevates mean arterial pressure via peripheral vasoconstriction and elevated systemic vascular resistance [63,64,[69][70][71]. A dose-response relationship for this phenomenon was recently reported across three metaboreflex exercise intensities [72]. Cardiac output was limited during metaboreflex activation because of increased coronary vasoconstriction in dogs with HFrEF, but this has yet to be confirmed in humans with HFrEF [73].…”
Section: Muscle Metaboreflex In Hfrefmentioning
confidence: 99%
“…In humans, isolation of the metaboreflex (primarily via postexercise circulatory occlusion following forearm exercise) has resulted in preserved and exaggerated blood pressure responses in HFrEF compared to healthy adults (with variable sympathetic nervous system activity responses reported) (Barrett-O'Keefe et al 2018;Carrington et al, 2001;Crisafulli et al 2007;Keller-Ross et al, 2014;Notarius et al, 2001;Piepoli et al 1996Piepoli et al , 1999Shoemaker et al 1998;Silber et al, 1998;Sterns et al, 1991). Despite these discrepancies, it is clear that the contribution of cardiac output and systemic vascular resistance to the metaboreflex-mediated blood pressure response is altered with the HF syndrome (Barrett-O'Keefe et al 2018;Crisafulli et al, 2007;O'Leary et al, 2004). For example, Barrett-O'Keefe et al reported the blood pressure, cardiac output, and systemic vascular resistance responses with isolated metaboreflex activation (via postexercise circulatory occlusion) following forearm exercise at 15%, 30% and 45% maximum voluntary contraction (Barrett-O'Keefe et al, 2018) (see Figure 4).…”
Section: Contribution Of Metabolically and Mechanically Sensitive Aff...mentioning
confidence: 99%